Actes de Vatopédi I. Des origines à 1329. Édition diplomatique par J. Bompaire, J. Lefort, V. Kravari, C. Giros. Texte-Album (Archives de l’Athos XXI), P. Lethielleux - Πολέμης, Ιωάννης Δ. (Μακεδονικά, 2002)
No abstract